Behaviorism Approach through Operant Conditioning: Motivating Students in English Speaking Class - Sahabuddin, Ilham; Rasyid, Asriadi; Maming, Khadijah; Sianna, Sianna; Wahyuddin, Wahyuddin (Journal of English Language and Education, 2025)
This study investigates whether applying behaviorist operant conditioning can better use reinforcement in EFL classrooms to increase students’ speaking confidence, skills, and motivation. Using a quasi-experimental, non-equivalent control-group design, an experimental class received reinforcement while a control class followed conventional instruction; pre/post tests and a Likert-scale motivation questionnaire were analyzed with t-tests. Results show significant gains for the experimental group: mean speaking scores rose to Satisfactory (82.37) versus the control’s Adequately outcome (69.12), score dispersion narrowed (SD 10.21 to 6.01), and post-test distributions shifted to Satisfactory. Motivation outcomes were robust, with most students reporting high motivation after reinforcement. We conclude that operant conditioning effectively strengthens desirable speaking behaviors, increases engagement, and reduces performance variability, offering a practical approach for speaking classes. Implications include integrating reinforcement, feedback, and repetition into classroom pedagogy to sustain gains.